Effect of dexmedetomidine on ncRNA and mRNA profiles of cerebral ischemia-reperfusion injury in transient middle cerebral artery occlusion rats model - Zhang, Zhen Zhen; Nasir, Abdul; Li, Dong; Khan, Suliman; Bai, Qian; Yuan, Feng (Frontiers in Pharmacology, 2024)
Ischemic stroke poses a significant global health burden, with rapid revascularization treatments being crucial but often insufficient to mitigate ischemia-reperfusion (I/R) injury. Dexmedetomidine (DEX) has shown promise in reducing cerebral I/R injury, but its potential molecular mechanism, particularly its interaction with non-coding RNAs (ncRNAs), remains unclear. This study investigates DEX's therapeutic effect and potential molecular mechanisms in reducing cerebral I/R injury. A transient middle cerebral artery obstruction (tMACO) model was established to simulate cerebral I/R injury in adult rats. DEX was administered pre-ischemia and post-reperfusion. RNA sequencing and bioinformatic analyses were performed on the ischemic cerebral cortex to identify differentially expressed non-coding RNAs (ncRNAs) and mRNAs. The sequencing results showed 6494 differentially expressed (DE) mRNA and 2698 DE circRNA between the sham (S) and tMCAO (I/R) groups. Additionally, 1809 DE lncRNA, 763 DE mRNA, and 2795 DE circRNA were identified between the I/R group and tMCAO+DEX (I/R+DEX) groups. Gene ontology (GO) analysis indicated significant enrichment in multicellular biogenesis, plasma membrane components, and protein binding. KEGG analysis further highlighted the potential mechanism of DEX action in reducing cerebral I/R injury, with hub genes involved in inflammatory pathways. This study demonstrates DEX's efficacy in reducing cerebral I/R injury and offers insights into its brain-protective effects, especially in ischemic stroke. Further research is warranted to fully understand DEX's neuroprotective mechanisms and its clinical applications.